2022
DOI: 10.52911/itall.1193910
|View full text |Cite
|
Sign up to set email alerts
|

Milenyumdan koronavirüs dönemine Türkiye'de çevrimiçi sınavlar üzerinde yapılan çalışmalara ilişkin bir inceleme

Abstract: With removing the time and place restrictions, online exams have an essential place in meeting the needs of the digital age. It has become a much-needed structure for measuring individuals' competence remotely, especially in emergencies such as during the coronavirus epidemic. However, there are problems in Turkish online assessment system. The researcher revealed online exams' status and identified their deficiencies in Turkey, and made suggestions. In the research, the articles and theses were examined made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…As a result, it is possible to say that the training process was adequate and the assignments given with infographics contributed to this (Jones et al, 2019). Alternative measurement tools and systems are needed for online environments (Albayrak, 2022). For this reason the research has shown that designing or using infographics is effective in students' learning processes (Tsai et al, 2020;Smith & Robertson, 2021;Çaka & Dursun, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it is possible to say that the training process was adequate and the assignments given with infographics contributed to this (Jones et al, 2019). Alternative measurement tools and systems are needed for online environments (Albayrak, 2022). For this reason the research has shown that designing or using infographics is effective in students' learning processes (Tsai et al, 2020;Smith & Robertson, 2021;Çaka & Dursun, 2022).…”
Section: Discussionmentioning
confidence: 99%